Prescription Opioids Are Associated With Population Mortality in US Deep South Middle-Age Non-hispanic Whites: An Ecological Time Series Study - Mark A. Brandenburg (Frontiers Media S.A., 2019)
Objective: The US Burden of Disease Collaborators reported that between 1990 and 2016, the top 10 states with increasing probability of death between the ages of 20 and 55 years were all in the South. A recent study of annual surveillance data found that increasing all-cause mortality rates were occurring in middle-age non-Hispanic whites. The vast proportion of all-cause mortality consists of medical causes, not external causes (i.e., overdose, mental illness, suicide, homicide, or motor vehicle crashes). It has been hypothesized by researchers that the ongoing opioid epidemic has an etiologic role in the trend of increasing medical death, but ecological studies looking for an association have not been published. The objective of this study was to test the hypothesis that hydrocodone and oxycodone sales are temporally associated and correlated with annual NHW45-54 medical-cause mortality rates in the Deep South region comprised of Alabama, Arkansas, Louisiana, Mississippi, Oklahoma, and South Carolina.Methods: Mortality and opioid sales data were obtained from the Centers for Disease Control and Prevention Wonder Detailed Mortality and University of Wisconsin State Health Access Data Assistance Center databases, respectively. Annual, state and regional NHW45-54 medical-cause mortality and opioid sales data were analyzed using Spearman rank correlation (rs) testing, after first and second differencing, in order to achieve stationarity and control for trend similarities.Results: Sales of prescription opioids follow very similar temporal patterns across these six states, with simultaneous increases in 2007 and 2013. With few exceptions, annual opioids sales trends were correlated state-to-state. Two prominent spikes are evident in the aggregated opioid sales trends of the six states, with both sales spikes preceding same-directional fluctuations in medical-cause mortality by ~1 year. After a 1 year adjustment of second-differenced data, population hydrocodone exposure was correlated with female NHW45-54 population medical-cause mortality [rs(13) = 0.540; P = 0.038]; and oxycodone exposure correlated with male NHW45-54 population medical-cause mortality [rs(13) = 0.607; P = 0.016].Conclusions: State sales of prescription hydrocodone and oxycodone in the six states studied follow non-random, systematic trajectories. A strong correlation and temporal association exists between prescription opioid sales and medical-cause mortality in this Deep South NHW45-54 population.